Persistent inflammation and endothelial dysfunction in patients with treated acromegaly. Issue 12 (December 2019) - Wolters, T L C; van der Heijden, C D C C; van Leeuwen, N; Hijmans-Kersten, B T P; Netea, M G; Smit, J W A; Thijssen, D H J; Hermus, A R M M; Riksen, N P; Netea-Maier, R T
Abstract : Objective: Acromegaly is characterized by an excess of growth hormone (GH) and insulin-like growth factor 1 (IGF1). Cardiovascular disease (CVD) risk factors are common in acromegaly and often persist after treatment. Both acute and long-lasting pro-inflammatory effects have been attributed to IGF1. Therefore, we hypothesized that inflammation persists in treated acromegaly and may contribute to CVD risk. Methods: In this cross-sectional study, we assessed cardiovascular structure and function, and inflammatory parameters in treated acromegaly patients. Immune cell populations and inflammatory markers were assessed in peripheral blood from 71 treated acromegaly patients (with controlled or uncontrolled disease) and 41 matched controls. Whole blood (WB) was stimulated with Toll-like receptor ligands. In a subgroup of 21 controls and 33 patients with controlled disease, vascular ultrasound measurements were performed. Results: Leukocyte counts were lower in patients with controlled acromegaly compared to patients with uncontrolled acromegaly and controls. Circulating IL18 concentrations were lower in patients; concentrations of other inflammatory mediators were comparable with controls. In stimulated WB, cytokine production was skewed toward inflammation in patients, most pronounced in those with uncontrolled disease. Vascular measurements in controlled patients showed endothelial dysfunction as indicated by a lower flow-mediated dilatation/nitroglycerine-mediated dilatation ratio. Surprisingly, pulse wave analysis and pulse wave velocity, both markers of endothelial dysfunction, were lower in patients, whereas intima-media thickness did not differ. Conclusions: Despite treatment, acromegaly patients display persistent inflammatory changes and endothelial dysfunction, which may contribute to CVD risk and development of CVD.